On the Dirichlet problem for the Beltrami equations in finitely connected domains - Kovtonyuk, D. A.; Petkov, I. V.; Ryazanov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We establish a series of criteria for the existence of regular solutions of the Dirichlet problem for degenerate Beltrami equations in arbitrary Jordan domains. We also formulate the corresponding criteria for the existence of pseudoregular and multivalued solutions of the Dirichlet problem in the case of finitely connected domains.